Pengaruh Pengungkapan Corporate Social Responsibility Pada Nilai Perusahaan dengan Likuiditas Sebagai Variabel Moderasi - Adi Putra, Ida Bagus; Astika, Ida Bagus Putra (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of corporate social responsibility disclosure on company value with liquidity as moderation variables. This research was carried out on mining companies listed on the Indonesia Stock Exchange in 2013-2016. The number of samples used in this study were 11 companies obtained by non-probability sampling technique with purposive sampling method. Data analysis techniques were carried out using moderated regression analysis analysis techniques. Based on the results of the study, shows that Corporate Social Responsibility has a significant positive effect on firm value. This study also found that liquidity was able to moderate the influence of Corporate Social Responsibility on corporate value. Keywords: corporate social responsibility, company value, liquidity